Effects of Glucose Fluctuation Targeted Intervention on the Prognosis of Patients with Type 2 Diabetes following the First Episode of Cerebral Infarction - Qingqing Lou; Xiaodan Yuan; Shujie Hao; Joshua D. Miller; Juan Yan; Panpan Zuo; Jianing Li; Lihong Yang; Hong Li (Journal of Diabetes Research)
Objective. The purpose of this study was to assess the effects of glucose fluctuation targeted intervention on neurologic function, independent living skills, and quality of life in type 2 diabetes patients following the first episode of cerebral infarction (CI). Methods. This was a randomized control trial. Following confirmed cerebral infarction, 75 patients with type 2 diabetes were randomized into 2 groups: control group (n=37) with usual care, focused on hemoglobin A1c (HbA1c) control, targeting A1c<7%, and intervention group (n=38), targeting both A1c<7%and daily glycemic fluctuation (largest amplitude of glycemic excursions (LAGE<80 mg/dL)). Results. After 6 months, data from 63 patients were analyzed (30 in the control group, 33 in the intervention group). There was no difference (P>0.05) in the reduction of A1c between the 2 groups, but the reductions of LAGE (P=0.030), 1,5-anhydroglucitol (1,5-AG) (P=0.023), 2-hour postprandial blood glucose (2hPG) (P=0.041), and low-density lipoprotein cholesterol (LDL-c) (P=0.046) were significantly different. The National Institutes of Health Stroke Scale (NIHSS) score of the intervention group was better than the control group (2.35±0.81 vs. 3.50±2.24, P=0.047). In terms of quality of life, there was no significant between-group difference in total Stroke Impact Scale (SIS) score, but in the intervention group, scores in the strength, hand function, and participation dimensions were higher than those in the control group (P=0.041, P=0.049, and P=0.048, respectively). Conclusion. Glucose fluctuation targeted intervention can improve nerve function for patients with T2DM following the first CI episode. This trial is registered with NCT03932084.